Strategi Pengembangan Kota Bandung sebagai Kota Kreatif Desain: Pendekatan SWOT - Hanan, Aliyyah; Anggraeni, Jesicca Dhea; Sholihah, Fia; Tita, Refoozan (LPPM Universitas Terbuka, 2025)
Bandung was designated as a UNESCO City of Design in 2015, recognizing its contribution to the creative economy, particularly in the field of design. However, the development of Bandung as a creative design city has not yet reached its full potential. Several creative infrastructures are poorly maintained, creative communities remain fragmented, and existing regulations have not been fully implemented. This study aims to formulate development strategies for Bandung as a creative design city using a qualitative descriptive approach and SWOT analysis. The research identifies internal factors (strengths and weaknesses) and external factors (opportunities and threats) through the IFAS and EFAS methods. The analysis indicates that Bandung falls into SWOT Quadrant I, suggesting a strong position with significant opportunities. Therefore, a progressive strategy is recommended everaging internal strengths such as regulations, communities, creative events, and supporting institutions to seize global collaboration opportunities, improve human resources, and promote the city’s creative profile. This strategy is implemented through training programs, incentives, digital promotion, and strengthened cross-sectoral and international collaboration. These findings highlight the importance of synergistic roles among government, communities, and institutions in realizing Bandung ’s vision as a leading global design hub.